Novel aspects to the structure of rabbit articular cartilage - ap Gwynn I.; Wade S.; Ito K.; Richards R. G. (European Cells & Materials, 2002)
Applying cryo and modified chemical preparation techniques, mainly for scanning electron microscopy, revealed entirely new aspects to the structure of the radial zone of rabbit tibial plateau articular cartilage. The aggrecan component of the extracellular matrix was contained radially in columns, each with a diameter of 1-3mm, by a tightly packed matrix of collagen fibrils. The collagen fibrils were arranged radially, some straight and others in an opposed spiral arrangement, with regularly repeating patterns. This organization existed in the regions surrounding the columns of chondrocytes, known as chondrons. The load bearing property of the tissue was explained by the directed flow and containment of the interstitial fluid, modulated by the protein-carbohydrate complexes, along these collagen bounded tubular structures. The reason why such a structure has not been described previously may be that it is not retained by aldehyde fixation followed by dehydration, the method commonly used for tissue preparation for electron microscopy.